DAYA TERIMA DAN KANDUNGAN GIZI (ENERGI, PROTEIN) GYOZA YANG DISUBSTITUSI KEONG SAWAH (Pila ampullacea) DAN PUREE KELOR (Moringa oleifera)[The Acceptability and Nutrient Content (Energy, Protein) of Gyoza Subtitute with Snail (Pila Ampullacea) and Puree Moringa (Moringa Oleifera)] - Nabillah Eka Permatasari; Annis Catur Adi (Universitas Airlangga, 2018)
Snail and moringa are the example of food that contain several nutrition such as energy, protein, calcium needed by stunted children. The purpose of this study was to analyze the effect of snail (Pila ampullacea) and puree moringa (Moringa oleifera) substitution toward the acceptance and nutritional value (energy and protein) of gyoza as an healthy snack alternative. This study was an experimental with complete random design study. Untrained panelists were 30 students of grade five student in elementary school Komplek Kenjeran II 506. Elementary school Based on scoring by panelist formula F3 is the best treatment formula, because it is better in color and texture aspect but it has no significant difference in aroma and taste compared with treatment formula. The Friedman Test showed there were significant differences in color, aroma, texture and taste (p<0.05). Result of Wilcoxon Signed Rank Test showed that overall test of control formulas and treatment formulas were having differences but the result between treatment formulas were not having significant differences. The highest energy and protein content were F3 224.8 g and 12.75 g/100 g gyoza. Based on the best acceptance value and the highest energy content, it was conclude that the optimization formula was F3 (75 g snail and 20 g moringa) as an alternative healthy snack for school-children.